Kazakhstan Soil Microbiome Scientific Data, Mendeley Data, v1 - Schönbach, Christian; Inglezakis, Vassilis; Yapiyev, Vadim; Gilman, Charles P.; Kabdullayeva, Tolganay; Suleimenova, Akmaral; Shagadatova, Aizhan; Duisembay, Azat; Naizabekov, Sanzhar; Mussurova, Saule; Sydykova, Kamilya; Raimkulov, Ilyas; et al. (Nazarbayev University School of Sciences and Humanities, 2018)
Kazakhstan is the largest land-locked country in the world. Its massive land area of 2.725 x 106 km² represents a huge reservoir for soil organic carbon (SOC) that is thought to play an important role in global climate-carbon modelling. Yet comprehensive SOC data on Central Asia and particularly Kazakhstan are scarce, resulting in considerable uncertainties to what extent soils of forests and steppe in the North and East and arid areas in the South and West contribute to sequestering atmospheric carbon or emitting carbon into the atmosphere. We assessed the current soil properties of Kazakhstan by sampling top soil (25 cm) at 40 sites between Petropavlovsk (North) and Taraz (South) during wet and dry seasons, and determined the top soils' physical and chemical compositions and related phenological properties at sampling sites. Supplement 1 contains a folder with photos of landscape and vegetation for each sample location. The naming convention is location number. photo number (date the sample was taken). For example, 1.1(25.05.15) corresponds to location 1 and photo 1 on May 25, 2015. Supplement 2 is a Microsoft Excel file that contains spreadsheets with data on 1) soilTC, soil total organic carbon (TOC), soil total inorganic carbon (TIC), 2) Loss on Ignition (LOI), 3) soilTN, 4) soil dry bulk density, 5) gravimetric and volumetric soil moisture 6) soil suspension and supernatant pH; 7) soil electrical conductivity, and 8) soil TOC and TN 9) annotation table (Table 1). Values of sample measurements from each location were reported with standard deviation (STDEV) and standard error (SE) when applicable.
Kazakhstan Soil Microbiome Scientific Data, Mendeley Data, v1